CONGENITAL SCOLIOSIS: AN ARTICLE REVIEW - Komang Agung Irianto; Hizbillah Yazid (Journal Orthopaedi and Traumatology Surabaya, 2019)
Background: Congenital Scoliosis (CS) defined as vertebral lateral deviation which forms during the intrauterine embryonic phase, carrying incidence between 0,5-1 per 1000 births. Mortality rate increases in untreated case, especially due to pulmonary problem (40%).Contents: CS can range from hemivertebrae (HV) which may be single or multiple, vertebral bar with or without HV, block vertebrae, wedge shaped or butterfly vertebrae. The risk factors for progression include: type of defect, site of defect, and the patient’s age. Plain radiographs remain standard diagnosis. MRI evaluation should be considered. The goal of managing CS is to obtain a balanced trunk and spine while maintaining as much normal spinal growth as possible and preventing neural deficit. Non-operative management is including observation, brace, and traction. The operative procedures are broadly divided into (a) those preventing further deformity: in situ fusion, convex hemiepiphysiodesis, and HV excision, (b) those that correct the present deformity: hemiepiphyseodesis & hemiarthrodesis, single & dual growing rods, HV excision, and reconstructive osteotomy.Conclusion: The treatment of CS remains one of the more challenging aspects of pediatric orthopaedic surgery. Operative treatment should be reserved for patients whom non-operative management didn’t meet the criteria or failed.